Effects of lipopolysaccharide infusion on feed intake, apparent digestibility, rumen fermentation and microorganisms of young Holstein bulls fed diets with different ratios of lysine and methionine - Wang, Huiyao; Liu, Hongyun; Pan, Shijia; Ma, Zhicong; Wang, Yanming; Liu, Jianxin; Wang, Chong; An, Zhigao (Frontiers in Veterinary Science, 2025)
The aim of this experiment was to investigate the effects of intravenous infusion of lipopolysaccharide (LPS) and feeding different ratios of lysine (Lys) and methionine (Met) on feed intake, apparent digestibility, rumen fermentation and microorganisms in young Holstein bulls. Five seven-month-old Holstein bulls with similar body weights (279 ± 42 kg) were selected and subjected to a 5 × 5 Latin square experiment. The control group (CON) was fed with basal diet and the ratio of Lys to Met in the diet was adjusted to 3.0: 1. The experimental groups were received LPS infusion while being fed the basal diet (TRT1), along with LPS infusion and the addition of rumen-protected lysine (RPL) and rumen-protected methionine (RPM) to make the ratio of Lys to Met to 2.5:1 (TRT2), 3.0:1 (TRT3) and 3.5: 1 (TRT4), respectively. The LPS jugular infusion dose was set at 0.01 μg/kg body weight on days 1–3 and 0.05 μg/kg body weight on days 4–7. The trial was conducted over five periods, consisting of a 7-day trial period and a 6-day interval. The results indicated that there were no significant effects of LPS infusion on feed intake and apparent digestibility in young Holstein bulls fed different ratios of Lys and Met (p > 0.05). The treatment had no significant effects on the pH and total volatile fatty acids (p > 0.05). Compared with CON, the acetate content in the experimental groups exhibited an increasing trend (p = 0.066), while the content of NH3-N decreased significantly (p < 0.05). LPS infusion had no significant effect on rumen microorganisms at either the species or phylum level (p > 0.05). However, feeding different ratios of Lys and Met could significantly increasing the abundance of Oribacterium (p < 0.05) and tended to increase the abundance of norank_f__norank_o__RF_39 at the genus level (p = 0.087). These findings suggest that adding RPL and RPM into the diet may enhance the rumen environment in young Holstein bulls. Under the conditions of this experiment, adding RPL and RPM can mitigate the negative effects associated with LPS infusion, with an optimal ratio of Lys and Met is 3.0:1.